2008
DOI: 10.1007/s11442-008-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis on summer precipitation field over Qinghai-Tibet Plateau from 1961 to 2004

Abstract: The summer day-by-day precipitation data of 97 meteorological stations on the Qinghai-Tibet Plateau from 1961 to 2004 were selected to analyze the temporal-spatial distribution through accumulated variance, correlation analysis, regression analysis, empirical orthogonal function, power spectrum function and spatial analysis tools of GIS. The result showed that summer precipitation occupied a relatively high proportion in the area with less annual precipitation on the Plateau and the correlation between summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Understanding the precipitation variability in the YTR basin, and its potential impacts on water management and control of water disasters, is vital for the sustainable development of Tibet. Many studies have analyzed precipitation variability in the YTR basin by considering its linear trends [ Zhang et al ., ; Xu et al ., ; Lu et al ., ]. However, they did not evaluate the nonstationary and nonlinear variability of precipitation and did not clarify the spatial difference in precipitation variability either.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the precipitation variability in the YTR basin, and its potential impacts on water management and control of water disasters, is vital for the sustainable development of Tibet. Many studies have analyzed precipitation variability in the YTR basin by considering its linear trends [ Zhang et al ., ; Xu et al ., ; Lu et al ., ]. However, they did not evaluate the nonstationary and nonlinear variability of precipitation and did not clarify the spatial difference in precipitation variability either.…”
Section: Introductionmentioning
confidence: 99%
“…The western area of Sichuan Province, which lies in the southeast portion of the Tibet Autonomous Region, showed the most significant increase in precipitation. Research by Lu et al (2008) has shown that the summer precipitation tendencies at stations differed from 1961 to 2004 over the TP. Most of the stations with increases were located in the southern and northeastern plateau.…”
Section: Introductionmentioning
confidence: 99%
“…The response relation between the climate change and the TP is one of the most important focuses of climatic change research at present Immerzeel et al, 2010;Biermann et al, 2014 . Some previous researches have revealed climatic changes of the TP based on precipitation, temperature, energy exchange and so on Liu and Chen, 2000;Xu et al, 2008;Tang et al, 2011;Lu et al, 2012;Wang, 2018 . However, the existing studies have also shown regional contrast in climate variations over the TP Lu et al, 2008;Li, 2011;Salama et al, 2012;Wang, 2018 .…”
Section: Introductionmentioning
confidence: 99%
“…Some previous researches have revealed climatic changes of the TP based on precipitation, temperature, energy exchange and so on Liu and Chen, 2000;Xu et al, 2008;Tang et al, 2011;Lu et al, 2012;Wang, 2018 . However, the existing studies have also shown regional contrast in climate variations over the TP Lu et al, 2008;Li, 2011;Salama et al, 2012;Wang, 2018 . It is very important to study the local climate change characteristics in the TP, such as precipitation days PDs tendencies in the southeast TP STP .…”
Section: Introductionmentioning
confidence: 99%